Technology, risk and social policy: An empirical investigation - Dario Guarascio; Stefano Sacchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper investigates the role of exposure to technological risk in shaping social policy preferences, specifically on support for universal basic income and means-tested generalised minimum income. Evidence is provided for Italy, to exploit the availability of high-quality data, allowing measures of two dimensions of technological risk. Objective risk hinges upon the degree of substitutability of one's occupation by machines, while subjective risk concerns a worker's perception of their substitutability. We posit that exposure to technological risk induces individuals to ask for protection, and thus increases support for social policy. We test two hypotheses: first, that exposure to objective risk of replacement by machines is correlated with support for both safety nets; second, that such effect is increased by high perception of risk. On the whole, results confirm a strong relationship between exposure to technological risk and support for social safety nets, once objective risk is disentangled from subjective perceptions. However, we find that such relationship only holds for men, while it cannot be confirmed for women.
Keywords: I3; J08; O33; 330; Technological change; routine occupations; social policy; generalised minimum income; universal basic income; safety nets